The Influence of Environmental Concerns and Online Reviews toward Purchase Intention of Electrical Vehicle in Jakarta - Hendharta, Cecelia Suprapti; Soesilo, Ferdinandus Winandy (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This research was conducted to examine the partial and simultaneous effects of Environmental Concerns (X1) and Online Reviews (X2) on Electric Vehicle Purchase Intention (Y) in Jakarta. A quantitative approach was employed, using a purposive sampling technique with a total of 155 respondents. Data was collected through the distribution of questionnaires measured using a Likert scale. The analysis included validity and reliability testing, along with multiple regression analysis, processed using SPSS 25. The results indicate that Environmental Concerns and Online Reviews simultaneously have a positive and significant influence on Electric Vehicle Purchase Intention. Therefore, it can be concluded that potential EV buyers in Jakarta are significantly influenced by these two factors when considering their purchase decisions.